Blended to satisfaction: Factors influencing student satisfaction in a language classroom / Er Ann Nah … [et al.] - Er, Ann Nah; Liaw, Shun Chone; Lim, Teck Heng; Marimuthu, Rasaya (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Learning environments have to evolve in tandem with the ever changing landscape of technology advancement. Face to face didactic in a formal classroom setting is not enough to stimulate and motivate learning. Thus, institutions of higher learning are investing in technology mediated learning environments to cater to students born in the digital age. With this in mind, a blended learning course was introduced to culinary students learning basic French in a local university. This study uses a questionnaire as a tool to investigate students’ level of satisfaction in a blended environment. The research focuses on four independent variables: learner to content interaction (LC), learner to instructor interaction (LI), learner to learner interaction (LL) and learner to technology interaction (LT). The results suggest that students’ perceived satisfaction level has a carry over effect in their scholastic performance and continuous persistent in developing their language skills.